Small Molecular Antibacterial Peptoid Mimics: The Simpler the Better - Ghosh, Chandradhish; Manjunath, Goutham B.; Akkapeddi, Padma; Yarlagadda, Venkateswarlu; Hoque, Jiaul; Uppu, Divakara S. S. M.; Konai, Mohini M.; Haldar, Jayanta (Journal of medicinal chemistry, 2014)
The emergence of multidrug resistant bacteria compounded by the depleting arsenal of antibiotics has accelerated efforts toward development of antibiotics with novel mechanisms of action. In this report, we present a series of small molecular antibacterial peptoid mimics which exhibit high in vitro potency against a variety of Gram-positive and Gram-negative bacteria, including drug-resistant species such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecium. The highlight of these compounds is their superior activity against the major nosocomial pathogen Pseudomonas aeruginosa. Nontoxic toward mammalian cells, these rapidly bactericidal compounds primarily act by permeabilization and depolarization of bacterial membrane. Synthetically simple and selectively antibacterial, these compounds can be developed into a newer class of therapeutic agents against multidrug resistant bacterial species.